Idiopathic lung fibrosis and anti myeloperoxidase glomerulonephritis: the tree that hides the forest. Issue 1 (December 2015) - Pineton de Chambrun, Marc; Nunes, Hilario; Brochériou, Isabelle; Hertig, Alexandre
Abstract Background Although anti-neutrophil cytoplasmic antibodies [ANCA] are frequently found in patients diagnosed with idiopathic pulmonary fibrosis [IPF], current guidance does not recommend serologic testing for vasculitis. Case presentation A 71-year old Caucasian male, diagnosed with IPF three years earlier, presented with rapidly progressive glomerulonephritis. ANCA were found both in current and historical sera. A kidney biopsy sample was taken, which revealed a pauci-immune glomerulonephritis, but also areas of glomerular fibrosis, hence strongly suggesting unrecognized flares of an indolent vasculitis in his past. This made the diagnosis of "idiopathic" pulmonary fibrosis very unlikely. Conclusion As nephrologists, we argue that testing for ANCA should be performed on a systematic basis, at least in elderly patients, even in the absence of extra-pulmonary signs of vasculitis at presentation.